Involvement of the Clock Gene period in the Circadian Rhythm of the Silkmoth Bombyx mori. Issue 3 (June 2019) - Ikeda, Kento; Daimon, Takaaki; Sezutsu, Hideki; Udaka, Hiroko; Numata, Hideharu
In Lepidoptera, the roles of period ( per ) and the negative feedback involving this gene in circadian rhythm are controversial. In the present study, we established a per knockout strain using TALEN in Bombyx mori, and compared eclosion and hatching rhythms between the per -knockout and wild-type strains to examine whether per is actually involved in these rhythms. The generated per knockout allele was considered null, because it encoded an extensively truncated form of PERIOD (198 aa due to a 64-bp deletion in exon 7, in contrast to 1113 aa in the wild-type protein). In this per knockout strain, circadian rhythms in eclosion and hatching were disrupted. Under LD cycles, however, a steep peak existed at 1 h after lights-on in both eclosion and hatching, and was considered to be produced by a masking effect—a direct response to light. In the per -knockout strain, temporal expression changes of per and timeless ( tim ) were also lost. The expression levels of tim were continuously high, probably due to the loss of negative feedback by per and tim . In contrast, the expression levels of per were much lower in the per knockout strain than in the wild type at every time point. From these results, we concluded that per is indispensable for circadian rhythms, and we suggest that the negative feedback loop of the circadian rhythm involving per functions for the production of behavioral rhythms in B. mori .